Analisis Faktor-faktor yang Mempengaruhi Minat Mahasiswa UNESA dalam Memilih Berkarir di BUMN Sebelum Masa Wisuda - Aulia, Aulia Siska Puspita Dewi; Maryam Bte Badrul Munir (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The escalating rivalry in the workforce necessitates that the younger generation, particularly students, possess exceptional qualities to thrive. State-Owned Enterprises (SOEs) are increasingly favored by Generation Z for their financial stability and perks; however, student interest is shaped by various aspects, including monetary compensation, certification quality, and the caliber of the MBKM program. Comprehending the determinants that affect UNESA students' inclination towards a career in SOEs prior to graduation is essential for enhancing human resource development in Indonesia. This study to examine the factors that affect the interest of Surabaya State University students in pursuing careers in State-Owned Enterprises prior to graduation. This study evaluates many elements, including financial incentives, certification quality, and the quality of the MBKM program, to ascertain career choices within the SOEs sector. The study employs a quantitative methodology and design. The purposive sampling method identifies the sample, resulting in a sample size of 101 pupils. Researchers gather primary data on a Likert scale ranging from 1 to 5, derived from a questionnaire that constitutes the focus of the study. This study encompasses many assessments, including the research instrument evaluation (validity and reliability), classical assumption testing, multiple linear regression analysis, coefficient of determination assessment, and hypothesis testing (t-test and F-test) utilizing SPSS version 25 software. The results reveals that financial incentives, certification quality, and MBKM quality significantly enhance Unesa students' enthusiasm in pursuing careers in state-owned enterprises (SOEs). The coefficient of determination indicates that 61.5% of the variation in student interest is explicable by the independent variables in the model.